2002
DOI: 10.1073/pnas.152264899
|View full text |Cite
|
Sign up to set email alerts
|

Previously uncharacterized genes in the UV- and MMS-induced DNA damage response in yeast

Abstract: A competitive growth assay has been used to identify yeast genes involved in the repair of UV-or MMS-induced DNA damage. A collection of 2,827 yeast strains was analyzed in which each strain has a single ORF replaced with a cassette containing two unique sequence tags, allowing for its detection by hybridization to a high-density oligonucleotide array. The hybridization data identify a high percentage of the deletion strains present in the collection that were previously characterized as being sensitive to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
92
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(103 citation statements)
references
References 34 publications
9
92
1
1
Order By: Relevance
“…The PP4cs complex is evolutionarily conserved and in yeast is composed of the Pph3, Ybl046w, and Psy2 proteins. The conservation in S. cerevisiae suggested a role for PP4cs in resistance to cytotoxic agents: genome-wide screens of the yeast deletion collection with the DNA-damaging agents cisplatin, oxaliplatin, mitomycin C, and methyl methanesulfate have highlighted the importance of both PPH3 and PSY2 in survival following exposure to these agents (10,38). We demonstrated that yeast strains deleted for YBL046W (PP4R2) are hypersensitive to cisplatin to the same extent as strains deleted for either PPH3 or PSY2.…”
Section: Fig 4 Psy2p Interacts With Rad53pmentioning
confidence: 84%
See 1 more Smart Citation
“…The PP4cs complex is evolutionarily conserved and in yeast is composed of the Pph3, Ybl046w, and Psy2 proteins. The conservation in S. cerevisiae suggested a role for PP4cs in resistance to cytotoxic agents: genome-wide screens of the yeast deletion collection with the DNA-damaging agents cisplatin, oxaliplatin, mitomycin C, and methyl methanesulfate have highlighted the importance of both PPH3 and PSY2 in survival following exposure to these agents (10,38). We demonstrated that yeast strains deleted for YBL046W (PP4R2) are hypersensitive to cisplatin to the same extent as strains deleted for either PPH3 or PSY2.…”
Section: Fig 4 Psy2p Interacts With Rad53pmentioning
confidence: 84%
“…Interestingly PPH3 deletion was also found to render cells hypersensitive to cisplatin treatment (10). Deletion of PPH3 or PSY2 was also reported to moderately increase the sensitivity of S. cerevisiae to methyl methanesulfonate (38). Because in mammalian cells PP4R2 is an obligatory partner for the association of PP4C and PP4R3, and Tip41 associates with PP4cs in yeast and mammals, we characterized the sensitivity of yeast lacking the YBL046W or TIP41 (YPR040W) genes to cisplatin treatment.…”
Section: ; See Below)mentioning
confidence: 99%
“…Other studies showed that Doa1 binds proteins containing UBX (Ub regulatory X) domains, such as Ubx4, Ubx6, and Ubx7 (7,43). Doa1 was first implicated as being part of the DNA damage response in a genome-wide screen for genes involved in repairing UV-and MMS-induced DNA damage (17). More recently, it was shown that LUB1, the Schizosaccharomyces pombe homologue of DOA1, plays a role in mediating the stress response (30).…”
mentioning
confidence: 99%
“…A chemical genomics screen for rapamycin sensitivity with deletion strains covering one-third of the yeast genome has previously been reported (6); this study explored the broad functions of the rapamycin-sensitive Tor pathways. In addition, screens of the yeast diploid deletion set have uncovered novel genes involved in resistance to ionizing radiation, UV, and methyl methanesulfonate (MMS)-induced DNA damage (7)(8)(9). Here, we report a whole-genome screen for altered sensitivity to wortmannin, a small-molecule modulator of the phosphatidylinositol (PI) metabolic pathway.…”
mentioning
confidence: 99%